OPTIMIZATION OF CONDITIONS FOR EXTRACTION OF COLLAGEN FROM THE SKINS OF BASA FISH (PANGASIUS HYPOPHTHALMUS) BY THE RESPONSE SURFACE METHOD - Tuan, Phan Dinh; Thu Huong, Le Thi; Dung, Nguyen Hoang (Vietnam Journal of Science and Technology, 2014)
Collagen has been used widely in the production of pharmaceutical and cosmetic products. Fishbased collagen has still more advantages than other sources of collagen and becomes an object of interested researches recently. Extraction and some properties of collagens from the skin of Pangasius hypophthalmus fish were investigated. Pepsin enzyme and acetic-acid solution was used as an extracting solvent. The optimal conditions for collagen extraction were determined by response surface methodology. The effects of four independent variables (pepsin enzyme content, acetic-acid concentration, liquid/solid ratio, and temperature) on the extraction yield of collagen from Pangasius hypophthalmus skin were evaluated. The optimal conditions to obtain the highest yield were determinded as follows: a pepsin enzyme content of 0.25%, a acetic-acid concentration of 0.75 M, a liquid/solid ratio of 80, a temperature of 14oC. The predicted yield was 73% which was in agreement with the actual value (P<0.05). The molecular weights of α1, α2 and β chains in collagen were estimated to be 115 and 125 and 240 kDa, respectively. Keywords: fish collagen, extraction, pangasius hypophthalmus